2020
DOI: 10.1038/s41598-020-72723-y
|View full text |Cite
|
Sign up to set email alerts
|

Inducible EphA4 knockout causes motor deficits in young mice and is not protective in the SOD1G93A mouse model of ALS

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by motor neuron loss that ultimately leads to fatal paralysis. Reducing levels or function of the tyrosine kinase, ephrin type-A receptor 4 (EphA4), has been suggested as a potential approach for slowing disease progression in ALS. Because EphA4 plays roles in embryonic nervous system development, study of constitutive knockout (KO) of EphA4 in mice is limited due to confounding phenotypes with homozygous knockout. We used a tamox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Studies have also found that during the development of the neuronal system, EphA4 plays a crucial role in axon guidance [ 31 , 32 ] and can also directly act on motor neurons to cause cell death [ 30 ]. Current studies have shown that EphA4 inhibitors have neuroprotective effects on Alzheimer's disease, spinal cord injury, and stroke in mouse models [ 33 ]. Our study found that double-luciferase results indicate that miR-98-5 targets EphA4; EphA4 is highly expressed in the neuronal cells induced by sevoflurane and the hippocampus of animal models ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also found that during the development of the neuronal system, EphA4 plays a crucial role in axon guidance [ 31 , 32 ] and can also directly act on motor neurons to cause cell death [ 30 ]. Current studies have shown that EphA4 inhibitors have neuroprotective effects on Alzheimer's disease, spinal cord injury, and stroke in mouse models [ 33 ]. Our study found that double-luciferase results indicate that miR-98-5 targets EphA4; EphA4 is highly expressed in the neuronal cells induced by sevoflurane and the hippocampus of animal models ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies in the SOD1(G93A) mouse model demonstrated that the heterozygous deletion of the EphA4 gene before birth improved survival (Van Hoecke et al, 2012). However, follow-up studies showed that 50% ubiquitous reduction of EphA4 at symptom onset did not improve survival (Dominguez et al, 2020;Rue et al, 2019b;Zhao et al, 2018). This suggests that the reduction of EphA4 levels is not sufficient to provide a therapeutic benefit.…”
Section: Introductionmentioning
confidence: 99%